Pelatihan Pemanfaatan Limbah Lidi Kelapa Sawit Menjadi Produk Kreatif di Rokan Hulu - Annisa Mardatillah; Sri Rezeki; Rosmayani Rosmayani (ABDI: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2022)
The abundance of potential resources from the oil palm plantation business creates business opportunities from upstream to downstream. Palm oil stick waste has not been explored optimally for its utilization so far it is only burned or thrown away to rot. The aim of this Community Service activity is to provide counseling and training on the use of palm oil stick waste into creative products of environmentally friendly woven crafts to a group of women in Kecepatan District, Rokan Hulu Regency, Riau to increase family income. The limited knowledge and skills of the partner groups in Kecepatan District, Rokan Hulu, Riau is a problem that limits the perception of business opportunities for partner groups in capturing potential business opportunities from palm oil stick waste. Basic counseling and training on making woven plate crafts from palm oil stick waste was carried out as a solution to the problems of the partner group. The result of this activity is an increase in the knowledge and skills of partner groups in utilizing palm oil stick waste into environmentally friendly creative products with high economic value so that they have the potential to increase family income.